Influence of Humic Substances on the Sorption Interactions between Lanthanide and Actinide Ions and Clay Minerals - B. Kornilovich; G. Pshinko; L. Spasenova; I. Kovalchuk (Adsorption Science & Technology)
Lanthanide (Eu, Nd, Gd) and actinide (Th, U) adsorption in a system consisting of fulvic acid, metal ions and clay minerals (montmorillonite, kaolinite, illite) was studied as a function of pH, metal ion concentration and fulvic acid concentration using spectrophotometric analysis and 152 Eu tracer methods. Increasing metal ion adsorption on to the clay minerals was observed when humic substances were present in the system. The bridging of polyvalent metal ions between clay minerals and humic substance complexes was proposed as the possible adsorption mechanism.